Estimation of the Change of Ovarian Cancer Incidence in Kazakhstan: Component Analysis of Its Dynamics with the Consideration of Ethnic Features - Ardak КUANYSHKALIYEVA; Nurbek IGISSINOV; Аsiya ТURGAMBAYEVA (Tehran University of Medical Sciences, 2016)
Background: We examined epidemiological aspects of dynamic changes in incidence of ovarian cancer in women of Kazakh and Russian nationalities in Kazakhstan. Methods: The material of investigation was primary data on registered patients with malignant ovarian tumors in the whole country. The study was conducted during the period of 1999-2009. Evaluation of changes in ovarian cancer incidence in the female population of Kazakhstan was performed using component analysis. Results: The number of patients with ovarian cancer in the whole country is increasing. This increase is due to several major reasons, including population growth (all females - ΔP=+22.1%, females of Kazakh nationality - ΔP=+46.0% and females of Russian nationality - ΔP=−259.3%), changes in the age structure (all females - ΔA=+32.7%, females of Kazakh nationality - ΔA=+27.1 and females of Russian nationality - ΔA=+130.8),and changes in risks of developing the disease (all females - ΔR=+36.0%, females of Kazakh nationality - ΔR=+13.1% and females of Russian nationality - ΔR=+246.8%). Conclusion: This investigation was the first epidemiological study of dynamics of ovarian cancer by component analysis in women of Kazakh and Russian nationalities in Kazakhstan. Implementation of the results of the study is recommended in management of anti-cancer activities for ovarian cancer.   Keywords: Ovarian cancer, Incidence, Ethnic groups, Component analysis